Noun phrase in Enets - Shluinsky, Andrey (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2020)
The paper presents a corpus-based description of the noun phrase structure in Enets dealing with both Enets dialects – Forest Enets and Tundra Enets. An Enets noun phrase has six slots for modifiers: determiner, relative clause, possessor NP, numeral, adjective phrase, apposed NP. Determiners, relative clauses, and adjective phrases are subject to linear recursion, other modifiers are not. All modifiers precede the head NP. In Enets, there is no agreement between head noun and modifiers, but numerals have different patterns in the choice of head noun number form. Kokkuvõte. Andrej Šluinski: Noomenifraas eenetsi keeles. Artikkel esitab korpuspõhise kirjelduse eenetsi keele noomenifraasi struktuurist mõlemas eenetsi keele murdes – metsaeenetsi ja tundraeenetsi. Eenetsi noomenifraasil on kuus täiendikohta: määratleja, relatiivlause, omajat väljendav NP, numeraal, omadussõnafraas, appositsiooniline NP. Määratlejad, relatiivlaused ja omadussõnafraasid alluvad lineaarsele rekursioonile, teised täiendid mitte. Kõik täiendid eelnevad põhisõnale. Eenetsi keeles puudub põhisõna ja täiendi ühilduvus, kui numeraalid nõuavad noomenifraasi põhisõnalt erinevaid arvuvorme. Аннотация. Андрей Шлуинский: Именная группа в энецком языке. В статье представлено выполненное на материале корпуса текстов описание структуры именной группы в обоих диалектах энецкого языка – лесном тундровом. Энецкая именная группа содержит шесть позиций для модификаторов вершинного существительного: детерминатор, относительное предложение, именная группа посессора, числительное, группа прилагательного, соположенная именная группа. Детерминаторы, относительные предложения и группы прилагательного подлежат линейной рекурсии, в отличие от других модификаторов. Все модификаторы предшествуют вершинному существительному. В энецком языке отсутствует согласование между вершинным существительным и модификаторами, но представлены разные модели выбора числовой формы вершинного существительного в именных группах с числительными.